2023
DOI: 10.1186/s12917-023-03577-5
|View full text |Cite
|
Sign up to set email alerts
|

Coxiella burnetii and its risk factors in cattle in Egypt: a seroepidemiological survey

Abstract: Animal production is greatly affected by Q fever. As a result of a lack of methodology and financial means to perform extensive epidemiological surveys, the disease's underdiagnosis has proven to be a challenge for effective control. The present study aimed to determine the seroprevalence of C. burnetii in cattle raising in four governorates situated at Nile Delta of Egypt and assess the associated risk factors for infection. A total of 480 serum samples were collected from cattle and examined for presence of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
1
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 50 publications
0
3
1
2
Order By: Relevance
“…In contrast, our survey reported lower seroprevalence values of C. burnetti in small and large ruminants than those reported in other studies in Upper and Lower Egypt (6.8 to 27%), respectively ( Table 1 ). Regarding the risk factors analysis, the seropositivity of C. burnetii in small ruminants was significantly higher than in large ruminants, which came in stark contrast with some previous reports from Egypt ( 63 ). This finding could be explained by the nature of grazing of small ruminants or by differences in the systems of management in this area, where large ruminants are mostly kept indoor, and therefore small ruminants could be more exposed to this pathogen along their life ( 64 ).…”
Section: Discussioncontrasting
confidence: 96%
“…In contrast, our survey reported lower seroprevalence values of C. burnetti in small and large ruminants than those reported in other studies in Upper and Lower Egypt (6.8 to 27%), respectively ( Table 1 ). Regarding the risk factors analysis, the seropositivity of C. burnetii in small ruminants was significantly higher than in large ruminants, which came in stark contrast with some previous reports from Egypt ( 63 ). This finding could be explained by the nature of grazing of small ruminants or by differences in the systems of management in this area, where large ruminants are mostly kept indoor, and therefore small ruminants could be more exposed to this pathogen along their life ( 64 ).…”
Section: Discussioncontrasting
confidence: 96%
“…Geographical differences could also be related to the density of cattle in the different geographical areas and to the effect of climate conditions [10,58]. Some studies confirmed that the amount of precipitation is inversely proportional to the incidence of coxiellosis, with rain acting as a protective factor by reducing the dust and the aerosolization of C. burnetii [59]. A marked variation in seroprevalence between different geographical areas of Northern Ireland have also been observed by McCaughey et al [57].…”
Section: Discussionmentioning
confidence: 82%
“…Although the remaining risk factors were not included in the multivariable model, they are mentioned in the literature in relation to seropositivity in dairy farms [10,42,[59][60][61][62][63][64]. In our study, the preliminary analysis suggested that there was greater probability of positive results when youngstock was sent to a heifer custom raising facility.…”
Section: Discussionmentioning
confidence: 91%
“…Moreover, certain breeds display increased susceptibility (Alsaadawy et al, 2023). Small ruminants can harbor and transmit the bacteria so contact with these animals represents another significant risk (Selim et al, 2023). Moreover, the transmission of C. burnetii by ticks amplifies this risk, highlighting the need for tick control measures.…”
Section: Introductionmentioning
confidence: 99%